How do patient-provider relationship continuity, gender, and language affect pediatric HPV vaccine acceptance? - Andrea N. Polonijo; Stephanie S. Lee; Nikita Nagpal; Rebecca Barros; Suellen Hopfer; Brandon Brown; Harry Pellman; Jasjit Singh (Taylor & Francis Group, 2021)
Increasing human papillomavirus (HPV) vaccine uptake remains a challenge. We compared reasons for HPV vaccine acceptance between two Southern California pediatric clinics serving diverse populations: an academically affiliated resident clinic that offered little continuity of care (n = 53) and a private-practice clinic with well-established physician-patient relationships (n = 200). We found strong doctor recommendation and information dissemination about the importance of HPV vaccination were the most important drivers of acceptance across these distinct settings. The top-cited reasons for vaccine acceptance also varied by gender, language (English vs. Spanish), and clinic type. Findings point to the need for (1) robust provider education on vaccines, vaccine-preventable diseases, and vaccine hesitancy and (2) increased efforts to raise public awareness of the importance of HPV vaccination.